SOREN KİERKEGAARD'IN AHLAK ANLAYIŞI - TURAN, RABİA (Fırat Üniveristesi, 2018)
Soren Kierkegaard, 19. yüzyılın başlarında yaşamış Danimarkalı bir düşünürdür. Döneminin sosyal ve dini kurumlarına yaptığı eleştirileriyle ün salmıştır. Eserlerinin değeri ancak 20. yüzyılın sonlarında anlaşılmaya başlanmıştır. Kierkegaard, melankoliyi yaşam tarzı haline getirmiştir. Sokrates'ten sonra en önemli ironist Soren Kierkegaard'dır. Kierkegaard, varoluşçuluk düşüncesinin temellerini atmıştır. Kierkegaard'a göre insan olmak doğuştan kazanılan bir özellik değildir. İnsan, kendini fark ederek insan olma sıfatını hak eder. Kierkegaard'ın oluşturduğu ahlak tanımlaması, din olgusu ile iç içedir. Kierkegaard, insan ahlakını üç başlık altında toplar. Bunlar; etik evre, estetik evre ve dini evredir. Estetik evre kişisel zevklerin peşinden koşan insanı, etik evre evrensel kurallara uyan insanı, dini evre ise kendini Tanrı'ya teslim etmiş insanı ifade eder. Ona göre varoluşun en üst basamağına çıkmış insan, İbrahim peygamberdir. Kierkegaard'ın ahlak anlayışı Fideizm anlayışıyla oluşturulmuştur. Fideizm, katı imancı ve teslimiyetçi anlayıştır. Kierkegaard'a göre insan, ancak Tanrı ile arasında kurulan yüce bağ sonucu mutluluğa ulaşır. İmana ulaşmak için kişinin öncelikle kendini keşfetmesi gerekir. Çünkü ancak ben olabilen insan hayatı her yanıyla kabullenir. İnsan gerçek mutluluğa ancak kendini Tanrı içine atarak ulaşabilir.

Soren Kierkegaard living in the early 19th century is a Danish Thinker. He becomes famous through his criticisms on the social and religious institutions. The value of his works is started to be understood at the end of 20th century. Kierkegaard makes melancholy lifestyle. He is the most important ironist after Socrates. Kierkegaard lays the foundation of existentialism. To Kierkegaard, being a human is not an innate characteristic. A human deserves the character of being a human by being conscious of himself. The definition of ethic defined by Kierkegaard is intertwined with the religion fact. Kierkegaard collects the morality of human under three stages. These are the ethical, the aesthetic and the religious. The aesthetic stage represents an individual going after personal pleasures, the ethical stage represents an individual obeying rules and the religious stage represents an individual submitting himself to God. To him, the prophet Abraham is the one reaching the top of existentialism. Kierkegaard's concept of ethic is constituted of the concept of Fideism. Fideism is a strict faith and submissive perception. To Kierkegaard, a person can achieve happiness through a supreme bond established between him and God. To reach faith, an individual should first discover himself. It is because of the fact that those who can become I accept life in all aspects. A human can reach real happiness only submitting to God.
Soren Kierkegaard's concept of ethic
Keywords: Din; Felsefe